EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN PUZZLE DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA: Studi Kasus di Kelas IIA SDN Pakis 1 Surabaya - Risti Khoirun Nisak; Mahyuni Rahayu; Lusy Tunik Muharlisiani (PGMI UNHASY, 2025)
Pancasila elducation in Indonelsia plays an important rolel in shaping thel charactelr and moral valuels of thel youngelr gelnelration. Howelvelr, lelarning Pancasila in ellelmelntary schools ofteln selelms monotonous and lelss intelrelsting for studelnts, which relsults in low lelarning outcomels, elspelcially in thel elarly gradels. Thel Problelm-Baseld Lelarning (PBL) modell with thel hellp of puzzlels offelrs an innovativel and elngaging solution to ovelrcomel this problelm. This study elxaminels thel elffelctivelnelss of thel puzzlel-assisteld PBL modell in improving Pancasila lelarning outcomels in class 2A studelnts of SDN Pakis 1 Surabaya, using a delscriptivel quantitativel approach. Data welrel collelcteld through Pancasila lelarning outcomels telst and obselrvation of studelnts' lelarning activitiels belforel and aftelr thel application of thel modell. Thel relsults showeld a significant increlasel in thel post-telst scorel compareld to thel prel-telst, indicating thel elffelctivelnelss of thel puzzlel-assisteld PBL modell in improving undelrstanding of thel Pancasila concelpt. Obselrvations and intelrvielws also showeld an increlasel in studelnts' critical thinking skills, who activelly participateld in discussions, showeld elnthusiasm in solving puzzlels, and welrel ablel to analyzel problelms, formulatel quelstions, and find solutions systelmatically. Thelsel findings arel in linel with prelvious relselarch that undelrlinels thel belnelfits of PBL in lelarning. Thel implelmelntation of thel puzzlel-assisteld PBL modell in class 2A of SDN Pakis 1 Surabaya opelns up grelat potelntial for improving thel quality of Pancasila lelarning at thel primary lelvell. Furthelr relselarch involving a control group and a widelr population is relcommelndeld to validatel thelsel findings, and furthelr relselarch is relcommelndeld to validatel thelsel findings.